Pengembangan Kompetensi Preseptor Klinis Keperawatan - Annisa Nur Erawan; Yunita Fitri Rejeki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to investigate the development of clinical nursing preceptor competencies in Cibabat Cimahi Regional Hospital. This research method uses descriptive qualitative with a phenomenological approach. The results showed that there were competency gaps in the form of 3 major themes in the development of clinical preceptor competencies as well as: a) the responsibilities of clinical counselors in guiding students, b) unpleasant experiences during guiding students, c) clinical counselors' expectations towards improving the student guidance process. The most relevant reinforcement model is preceptorship training. In conclusion, the competency gap that exists in clinical nursing supervisors at Cibabat Cimahi Regional Hospital is the responsibility of clinical counselors, unpleasant experiences while guiding students and clinical advisors' expectations towards improving student guidance processes. The strengthening model that is relevant to the essence of the competency gap in the four competencies of clinical preceptor competency is preceptorship training in collaboration with the Hospital. Keywords: Competence, Preceptorship